2019
DOI: 10.21037/jtd.2019.11.13
|View full text |Cite
|
Sign up to set email alerts
|

The association between plasma fibrinogen levels and lung cancer: a meta-analysis

Abstract: Background: Published studies have presented an inconsistent association between plasma fibrinogen level and poor prognosis or clinicopathological characteristics in lung cancer. Methods: In the absence of significant quality difference, combined hazard ratios (HRs) and their corresponding 95% confidence intervals (CIs) were calculated according to overall survival (OS), progression-free survival (PFS) and disease-free survival (DFS). Risk ratio (RR), odds ratio (OR) and standardized mean difference (SMD) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Furthermore, a multicenter prospective study on 395 patients with operable NSCLC showed that some elevated preoperative coagulation factors, such as fibrinogen, may have a significant effect on poor progression‐free survival and can be used to predict the prognosis of patients with NSCLC after surgery 19 . Even in a meta‐analysis of the association between plasma fibrinogen levels and lung cancer, plasma fibrinogen was considered a marker of prognosis and associated with distant metastasis and tumor stage 20 . This study focused on whether fibrinogen is a prognostic factor in patients with resected stage I NSCLC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a multicenter prospective study on 395 patients with operable NSCLC showed that some elevated preoperative coagulation factors, such as fibrinogen, may have a significant effect on poor progression‐free survival and can be used to predict the prognosis of patients with NSCLC after surgery 19 . Even in a meta‐analysis of the association between plasma fibrinogen levels and lung cancer, plasma fibrinogen was considered a marker of prognosis and associated with distant metastasis and tumor stage 20 . This study focused on whether fibrinogen is a prognostic factor in patients with resected stage I NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…19 Even in a meta-analysis of the association between plasma fibrinogen levels and lung cancer, plasma fibrinogen was considered a marker of prognosis and associated with distant metastasis and tumor stage. 20 This study focused on whether fibrinogen is a prognostic factor in patients with resected stage I NSCLC. Further, we recently found that elevated fibrinogen level was a significant prognostic factor even in stage I NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, peripheral blood coagulation parameters, which mirror the systemic coagulation state, hold promise as potential indicators for tumor risk stratification. The levels of coagulation markers have been found to be significantly correlated with the clinicopathological features of malignancies, such as gastric cancer, breast cancer, and lung cancer 11 13 . However, a paucity of research has investigated the correlation between coagulation markers and the clinicopathological features of PCa.…”
Section: Introductionmentioning
confidence: 99%
“…As a marker of systemic inflammation, PF is often associated with haemostasis and plays a key role in tumour research [ 21 , 22 ]. The pretreatment PF level has been shown to predict oncologic outcomes for digestive system tumours, lung carcinoma, gynaecologic carcinoma, and glioblastomas, but studies of its prognostic value in BC are lacking [ 18 , 23 , 24 , 25 ]. Additionally, at this stage, the potential molecular mechanism of PF affecting tumorigenesis remains controversial.…”
Section: Introductionmentioning
confidence: 99%